Bioluminescence-based detection of Klebsiella oxytoca VN13 in the environment - Kozyrovska, N.A; Alexeyev, M.F.; Kovtunovich, G.L.; Gun'kovska, N.V.; Kordyum, V.A. (Биополимеры и клетка, 1994)
The continuous expression of the Photobacterium leiognathi 54D10 lux genes coding for the bioluminescence was obtained in Klebsiella oxytoca VN13. Chromosomally and plasmid-encoded bioluminescence of strains constructed was used to monitor their survival in the barley rhizosphere during a limited field introduction in parallel with the parental strain. Lux+ Derivatives of K. oxytoca VN13, carrying the bioluminescence reporter plasmids survived on roots during the whole vegetative period of the plant and were not isolated from soil. Конститутивну експресію lux-генів Photobacterium leiognathi 64D10, що кодують біолюмінесценцію, отримано в бактерії Klebsiella oxytoca VN13. Для спостерігання за виживанням бактерії у ризосфері ячменю в польових експериментах було сконструйовано штами з закодованою в хромосомі або плазміді біолюмінесценцією. Похідні K. oxytoca VN13, які містили плазміди з біолюмінесцентною ознакою, виживали на коренях ячменю протягом усього періоду вегетації рослини, але їх не було виявлено в грунті. Конститутивную экспрессию lux-генов Photobacterium leiognathi 64D10, кодирующих биолюминесценцию, получено в бактерии Klebsiella oxytoca VN13. Для наблюдения за выживанием бактерии в ризосфере ячменя в полевых экспериментах было сконструировано штаммы с закодированной в хромосоме или плазмиде биолюминесценцией. Производные K. oxytoca VN13, содержащие плазмиды с биолюминесцентные признаком, выживали на корнях ячменя в течение всего периода вегетации растения, но их не было обнаружено в почве.